Studying Success and Failure Factors and their Phenomenon in Business Process Reengineering Projects in Iran Using Holistic Framework - Ahmad Alibabaei; Mohammad Aghdasi; Behrouz Zarei (Journal of Information Technology Management)
Business Process Reengineering (BPR) is one of the concepts, which consider process orientated view and promises significance successes. Since this concept is multidisciplinary, success in this endeavour requires considering different factors. However, a number of studies have been conducted to identify these factors; specific conditions of Iranian organization raise the need of studying the success factors in Iranian organizations with considering holistic view and their indications. In this paper, case study method has been used for studying different projects in Iran and then data has been analyzed by Content Analysis in order to extract the success factors in Iranian organizations and their phenomenon. Finding of this research can be considered for customization of the holistic framework and also can be useful for stakeholders involved in BPR initiatives, in adequately planning the initiative and checking the progress during the implementation.